Studying the Association Between Systolic Blood Pressure and Thyroid Stimulating Hormone in Newly Diagnosed Subclinical Hyperthyroidism Female Patients - Hami, Mohammed Abdulwahid; Jawzal, Kazheen Hussein; Mohammed, Lina Yousif; Ibrahiem, Aveen Akram (Science Journal of University of Zakho, 2022)
Background: Subclinical hyperthyroidism is a condition in which thyroid stimulating hormone (TSH) is mildly decreased with both free iodine thyroxine (free T4) and triiodothyronine (T3) within the normal range. The aim of this research is to determine the association between TSH with lipid profiles, age, blood pressure and body mass index (BMI) and also to evaluate lipid profiles in subclinical hyperthyroid patients.Materials and Methods: Ninety patients with subclinical hyperthyroidism were chosen as the patient group and 50 healthy individuals age-matched were chosen as the control group. Thyroid function tests TSH, T4 and T3 were performed by VIDAS and on the same day lipid profiles were performed by (Biolis 24i Premium) in the laboratory of General Zakho Hospital, Kurdistan Region, Iraq.Results: In subclinical hyperthyroidism the BMI and diastolic blood pressure values were non-significantly low (P=0.13 and p=0.27 respectively) whereas systolic blood pressure increased slightly but was still non-significant. TSH was significantly and negatively related to systolic blood pressure.Conclusion: Lipid profiles and systolic and diastolic blood pressure are not altered in subclinical hyperthyroidism. However, systolic blood pressure is related to the severity of the decrease in TSH levels.
Keywords: Subclinical hyperthyroidism, Dyslipidemia, Thyroid, Hormone, Blood pressure.